Analisis penularan, ketahanan varietas cabai (Capsicum spp) dan identifikasi genetik DNA isolat hasil inokulasi PepYLCIV dengan serangga kutukebul di Sulawesi Tenggara - Widodo, Catur Joko Widodo; Amartani, Kallis; Taufik, Muhammad (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Analysis of transmission, resistance of chili varieties (Capsicum spp) and genetic identification of DNA isolates resulting from PepYLCIV inoculation with whitefly insects in Southeast Sulawesi. Disease PepYLCIV (twin virus) is a cause of disease in chili plants that can lead to crop failure. The objectives of this study were to examine the effectiveness and damage to chili plants due to PepYLCIV infection through whitefly insect transmission, to examine the resistance reactions of several chili varieties to PepYLCIV disease, and to genetically identify the DNA of PepYLCIV symptoms resulting from transmission by whitefly insect vectors. The study was conducted in (screen house) resistant to whitefly insects. The method used is a Randomized Block Design (RAK), the treatment in the transmission test is K0 = No inoculation of vector insects (control); K1 = Inoculation of one vector insect; K3 = Inoculation of three vector insects; K5 = Inoculation of five vector insects and the treatment in the resistance test of chili varieties, namely V1: Cayenne pepper variety Sret, V2: Curly chili variety Lado F1 and V3: Large chili variety Pilar F1 and each was given 5 whitefly insects from the propagation. Genetic identification of DNA PepYLCIV isolates resulting from transmission using PCR techniques. The results showed that 3 whitefly insects had effectively transmitted and caused damage to chili plants aged 3 MSI, but one insect could already cause symptoms; Cayenne pepper variety Sreet has a higher level of resistance compared to large red chili varieties Pil F1 and curly chili varieties Lado F1 and the isolate resulting from transmission and resistance was positively infected with PepYLCIV with a DNA fragment size of 580 bp